2017
DOI: 10.1002/adom.201700496
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Plasmonic Modes in Multilayer Trench Grating Structures

Abstract: brings about a high potential application value in many fields such as plasmonic photocatalyst, [6,7] nonlinear optics, [8,9] surface-enhanced spectroscopy, [10,11] solar cells, [12,13] high integration optical devices, [14,15] and metamaterials, [16,17] etc. Among various basic plasmonic structures, the metal-insulator-metal (MIM) configuration that the insulator film is sandwiched between two symmetric metal films is one of the most common units. [18] In this structure, the electric field is strongly constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The five alternate Al and Si films formed two MIM waveguides in the multilayer grating stripe to sustain a gap plasmon mode with a relatively large propagation range 24 , 30 . Reflection was observed at the gap terminations due to the finite length of the waveguide, thereby resulting in the formation of an inner standing wave, which is a typical F-P resonance system with two distinct features, specifically, frequency sensitivity and multiple resonance orders 34 . The order of this F-P resonance mode is simply expressed as follows 35 , 36 : where φ r is the phase shift at the gap termination, which can be obtained by the linear fitting method, and β is the complex propagation constant, which can be calculated using dispersion equations derived from the symmetric waveguide theory with respect to the regular symmetric MIM waveguide, as carefully explained in our previous work 34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The five alternate Al and Si films formed two MIM waveguides in the multilayer grating stripe to sustain a gap plasmon mode with a relatively large propagation range 24 , 30 . Reflection was observed at the gap terminations due to the finite length of the waveguide, thereby resulting in the formation of an inner standing wave, which is a typical F-P resonance system with two distinct features, specifically, frequency sensitivity and multiple resonance orders 34 . The order of this F-P resonance mode is simply expressed as follows 35 , 36 : where φ r is the phase shift at the gap termination, which can be obtained by the linear fitting method, and β is the complex propagation constant, which can be calculated using dispersion equations derived from the symmetric waveguide theory with respect to the regular symmetric MIM waveguide, as carefully explained in our previous work 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this IMI configuration can be simplified to the interface between Al and air because the light hardly penetrated the first Al film. In addition, the energy was largely concentrated in the cavity of the trench, thereby resulting in the presence of the cavity resonance mode, which is another SPP mode with multiple resonance orders 34 . However, the present study only observed the first order in the concerned waveband.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Si grating structure coated with a multilayer HMM has been realized [73,74] as illustrated in Fig. 5(d).…”
Section: Hypercrystalsmentioning
confidence: 99%
“…(c) Ag/Al 2 O 3 multilayer HMM with grating and quantum dots layer embedded[72]. (d) Cross-section of a trench structure covered with Al/Si multilayer HMM[73,74]. The hypercrystals consist of small Λ 1 and large periods, Λ 2 , respectively.…”
mentioning
confidence: 99%